(untitled) (African Journal of Biomedical Research, 2021)
Replicating microorganisms at wound sites pose great health risks to humans especially due to increasing evolution of antimicrobial resistance to several antibiotics. Gnetum africanum has been used in ethnomedicine for successful management of wound infections and facilitation of the wound healing process. This study aimed at investigating the antimicrobial activity of leaves of G. africanum on bacterial isolates from wounds of diabetic patients. Antibiogram of twenty-six wound isolates was determined using disc diffusion method. Qualitative and quantitative phytochemical analysis of dried pulverized leaves was carried out. Succesive gradient extraction of dried pulverized leaves was done with hexane, ethyl acetate and methanol. Bioassay-guided fractionation of methanol extract was carried out using vacuum liquid chromatography (VLC). Antimicrobial activities of the leaf extracts and fractions of G. africanum were screened by agar-well diffusion. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were determined by agar-dilution. Bactericidal kinetics of the methanol extract was investigated using the viable count technique. Phytochemical screening detected saponins, alkaloids, tannins, phenols, anthraquinones and flavonoids, with minimal steroidal content. At 100 mg/ml, zones of inhibition ranged from 12-23 mm for all the extracts. MIC values ranged from <0.156->10 mg/mL for the crude extracts while the MIC values for the fractions ranged from 3.125-50 mg/mL. The kill kinetics showed a potent bactericidal activity which was concentration dependent with methanol extract. The study has shown that G. africanum extracts possess appreciable bactericidal activity and can be used in the management and treatment of wound infections.